Limited changes in the fecal microbiome composition of laying hens after oral inoculation with wild duck feces. (20th September 2019) - Schreuder, Janneke; Velkers, Francisca C; Bouwstra, Ruth J; Beerens, Nancy; Stegeman, J Arjan; de Boer, Willem F; Elbers, Armin R W; van Hooft, Pim; Feberwee, Anneke; Bossers, Alex; Jurburg, Stephanie D
ABSTRACT: Interspecies transmission of fecal microbiota can serve as an indicator for (indirect) contact between domestic and wild animals to assess risks of pathogen transmission, e.g., avian influenza. Here, we investigated whether oral inoculation of laying hens with feces of wild ducks (mallards, Anas platyrhynchos ) resulted in a hen fecal microbiome that was detectably altered on community parameters or relative abundances of individual genera. To distinguish between effects of the duck inoculum and effects of the inoculation procedure, we compared the fecal microbiomes of adult laying hens resulting from 3 treatments: inoculation with wild duck feces (duck), inoculation with chicken feces (auto), and a negative control group with no treatment. We collected cloacal swabs from 7 hens per treatment before (day 0), and 2 and 7 D after inoculation, and performed 16S rRNA amplicon sequencing. No distinguishable effect of inoculation with duck feces on microbiome community (alpha and beta diversity) was found compared to auto or control treatments. At the individual taxonomic level, the relative abundance of the genus Alistipes (phylum Bacteroidetes ) was significantly higher in the inoculated treatments (auto and duck) compared to the control 2 D after inoculation. Seven days after inoculation, the relative abundance of Alistipes had increased in the control and no effect was found anymore across treatments. These effects might be explained by the perturbation of the hen's microbiome caused by the inoculation procedure itself, or by intrinsic temporal variation in the hen's microbiome. This experiment shows that a single inoculation of fecal microbiota from duck feces to laying hens did not cause a measurable alteration of the gut microbiome community. Furthermore, the temporary change in relative abundance for Alistipes could not be attributed to the duck feces inoculation. These outcomes suggest that the fecal microbiome of adult laying hens may not be a useful indicator for detection of single oral exposure to wild duck feces.